ANALISIS BEBERAPA STATUS KIMIA TANAH DI LAHAN PERTANIAN BAWANG MERAH (Allium ascalonicum L.) DI DESA MAKU - Faizal Arief M; Isrun Isrun; Rahmat Zainuddin (Universitas Tadulako, 2018)
Shallot of LembahPalu variety is one of prioritized commodities in Central Sulawesi and is a raw material for fried onion processing industry which has become a local brand for Palu city. This variety is unique different from other varieties as shown by its dense texture bulb resulting in crunchy, tastefuland unchangeable aroma when kept sealed for a long period of time. The objective of this research was to determine the nutrient status under shallot plantation in Maku village, Dolo sub district of Sigi district. Survey was conducted on the research location where soil samples were taken purposively. Low soil C-organic of 0.97 – 0.70% was found due to their intensive cultivation. Soil pH was relatively neutral ranging from 7.4 – 7.6 cmol(+) kg-1. The content of soil P-total and K-total was low varying between 17.18-15.06 mg 100g-1 and between 11.84-11.01 mg 100g-1, respectively. The soil CEC was also low around 5.91-4.08 cmol(+)kg-1.Keywords: LembahPalu shallot, and soil chemical status.